(untitled) (Journal of the College of Basic Education, 2022)
Research into preparation training exercises for some motor skills and body mass index for children with mental disabilities. As well as identifying the effect of rehabilitative exercises, stomach in some motor skills and body mass index for children with mental disabilities. Either the search premise were statistically significant differences between pre tests in some motor skills and body mass index for children with mental disabilities. The researcher used experimental method design group, the sample was selected by intentional way of children with mental disabilities enrolled in the Institute of llouk and Rami, who range from their intelligence (50-70) a degree of mental disability mental age varies between simple (6-9) years of age (12-14) and numbered year (20). tribal tests were then the software application and then apply after tests and the results were processed statistically and asttentgt researcher that rehabilitative exercises prepared by researcher positive influence in the development of motor abilities in question, the results demonstrated significant moral differences between tribal interest waladet tests gateway rehabilitation exercises also prepared by researcher contributed to decreased body mass index which helped the sample to perform motor skills better. The researcher found to adopt rehabilitative exercises stomach as a platform for studying in institutes of mental disabilities. And allocate at least three days a week of exercise rehabilitation for mental disabilities. Similar research on other samples using rehabilitative exercises prepared by the researcher.